A LEGAL ANALYSIS OF FRAUD IN ONLINE TRANSACTIONS - Moh. Harish Reza Cahyo Sutartono; Nur Handayati; M. Syahrul Borman; Dudik Djaja Sidarta (Sekolah Tinggi Ilmu Hukum Awang Long, 2026)
Advances in information and communication technology have driven an increase in online buying and selling activities among the public. The convenience of electronic transactions has had a positive impact on commercial activities; however, it has also given rise to various legal issues, one of which is the criminal offense of fraud in online transactions. Such fraud is generally committed through social media, marketplaces, or other digital platforms using fake identities, false information, or deceptive tactics that result in financial losses for consumers. This study aims to analyze the legal framework governing criminal fraud in electronic transaction-based buying and selling and to examine the relationship between the provisions of Law No. 1 of 2023 on the Criminal Code and the Law on Information and Electronic Transactions in addressing online buying and selling fraud. The research method used is normative legal research with a legislative approach and a conceptual approach. The results of the study indicate that criminal acts of fraud in online sales and purchases are regulated in Articles 492, 493, 495, and 497 of the Criminal Code, while in electronic transactions, they are also related to the provisions of the Electronic Information and Transactions Law.